Stay with me - Adebayo, Ayobami, 1988- (New York : Alfred A. Knopf, 2017)
"A novel about a married Nigerian couple who must grapple with staggering levels of loss and betrayal in their quest to create a family for themselves" --
"This Is A Borzoi Book."
Keywords: Married people -- Fiction; Parent and child -- Fiction; Loss (Psychology) -- Fiction; Nigeria -- Fiction; Domestic fiction; Psychological fiction